$1!7o!Xls - Zuoqiu, Ming (Salt Lake City, UT : Project Gutenberg, 2007)
"$1!7o!Xl(B" by Ming Zuoqiu is a historical account written in the late 19th century. The book serves as a discourse on the political and moral philosophies of ancient China, weaving narratives about prominent figures and events that highlight the importance of virtue, governance, and the relationship between rulers and the people. The text promises to explore various themes related to leadership, ethics, and the historical context of the Zhou dynasty. The opening of "$1!7o!Xl(B" presents a series of philosophical dialogues and historical anecdotes where characters such as King Mu and various advisors engage in discussions about the duties and responsibilities of rulers. It examines the contrast between virtuous governance and tyranny, using allegories from past rulers to illustrate the consequences of moral failure. Through these initial reflections, the text establishes a framework for understanding the lessons of the past in political ethics, suggesting the enduring relevance of these discussions for both rulers and subjects. (This is an automatically generated summary.)s
Release date is 2007-12-19
Produced by Mistar Jiang
Keywords: China -- History -- Spring and Autumn period, 722-481 B.C.